GAMBARAN CAREGIVER TERHADAP INTERAKSI TEMAN SEBAYA PADA ANAK PENYANDANG AUTIS - Fajar Nugroho; Siswati Siswati; Tri Puji Astuti (Faculty of Psychology, Diponegoro University, 2013)
Autism has significance influence to communication, social interaction, imagination, and attitude. One of development task for children is to learn having peer friends and when school age peer have more influence than teacher or parents. Interaction between child and his peer is a dynamis relationship between two or more people and one attitude can influence or change others. Purpose of this study is to understand interaction between autism children with their friends in the view of caregiver.This research is held with qualitative method and used descriptive approach. Subject in this research are autistic child with his care giver as informan. Researcher used interview as primary method to get the data with observation and field record to get secondary data.Based from the data we can conclude interaction between autistic child and his friend is influence by his language ability. Researcher suggest to held language training so that children with autistic could had good interaction with their friends.